An integrative approach to bilingual cognition: preliminary insights into phonetic learning and sensorimotor adaptation - Laura Spinu; Laura Spinu; Yasaman Rafat; A. Duke Shereen; Bradley P. Sutton; Maida Percival; Anastasiia Myslyk; Jiyoon Kim (Frontiers in Human Neuroscience)
IntroductionThis study investigates the cognitive consequences of bilingualism by examining phonetic learning, speech motor adaptation, and verbal memory.MethodsEarly Spanish-English bilinguals divided into high and intermediate proficiency groups and English monolinguals completed three tasks: (1) production of an artificial English accent with novel phonotactic rules, (2) serial digit span in English, and (3) production of unfamiliar speech sounds during real-time magnetic resonance imaging (rtMRI).ResultsBilinguals, particularly those with high proficiency, outperformed monolinguals in phonetic and articulatory learning. In the memory task, no group-level differences emerged overall, but high bilinguals showed stronger primacy effects at moderate sequence lengths, suggesting more efficient encoding.DiscussionThese results support a shift toward investigating task-specific and process-based effects of language experience. We also demonstrate the feasibility of using rtMRI to assess articulatory behavior in cognitive studies of bilingualism, with minimal need for manual post-processing.